Kinetics of hexene-1 polymerization using [(N,N `-diisopropylbenzene)-2,3-(1,8-napthyl)-1,4-diazabutadiene] dibromonickel/methylaluminoxane catalyst system - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
{Kinetics of hexene-1 polymerization was investigated using [(N,N'-diiso-propylbenzene)2,3-(1,8-napthly)-1,4-diazabutadiene]/dibro monickel/methylaluminoxane catalyst. Experiments were performed at varying catalyst and monomer concentrations in the temperature range of -10 to 35 degrees C. First order time-conversion plot shows a downward curvature at temperatures of 20 degrees C and 35 degrees C indicating the presence of finite termination reactions. A nonlinear plot of degree of polymerization (P-n) with respect to conversion indicates occurrence of transfer reactions and slow initiation. The experimental molar masses are higher than predicted, which implies that a fraction of catalyst species could not be activated or is deactivated at the early stages of the reactions. The efficiency of the catalyst (Cat(eff)) varies from 0.77 to 0.89. The observed polydispersity of the poly(hexene-1) s is in the range of 1.18-1.48. The reaction order was found to be 1.11 with respect to catalyst. The Arrhenius plot obtained using the overall propagation rate constant, k(p), at five different temperatures (-10, 0, 10, 20, and 35 degrees C) was found to be linear with an activation energy
Keywords: Activation energy; chain transfer; degree of polymerization; hexene-1; kinetics (polym.); nickel (alpha-diimine)